Cryotherapy: An Alternative to Surgical Adjunct - Sushmita Paul (Institute of Medico-legal Publications Pvt Ltd, 2020)
The application of low controlled temperatures had advanced in recent years in many branches of surgery.Cryotherapy has opted as an option to destroy cancerous cells in mostly the head and neck region. In manycutaneous conditions, it has been productively used. It is a therapeutical process in which tissue inflammatoryand destructive response is done by freezing. Hence, it deliberately destroys tissue by using severe cold.Mouth is reasonably accessible due to oral mucosa’s moist surface that is well suitable for the application ofcryoprobe. We will discuss how cryotherapy can be used instead of surgical procedures.